THE EFFECT OF WORKLOAD AND TIME PRESSURE ON THE AUDITOR’S ABILITY TO DETECT FRAUD TENDENCIES AT THE REGIONAL REPRESENTATIVE AUDIT BOARD - Husin Husin; Nitri Mirosea; Amelia Sari (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of workload and time pressure on the auditor's ability to detect fraud tendencies. The population in this study were all State Civil Servants (ASN) at the Audit Board of the Province of Southeast Sulawesi, totaling 106 people. Data collection techniques in this study used a questionnaire which was measured using a Likert scale. The sampling technique used is a purposive sampling technique which has criteria, namely the position of auditor/investigator totaling 80 people. The number of auditors who filled out the questionnaire was 60 people. The results of this study indicate that: 1) Workload has a positive and insignificant effect on the Auditor's Ability to Detect Fraud Tendencies. 2) Time Pressure has a positive and significant effect on the Auditor's Ability to Detect Fraud Tendencies. 3) Workload and Time Pressure have a significant effect on the Auditor's Ability to Detect Fraud Tendencies.